The Color Fastness and Quality of Eco-Printed Leather with Different Types of Mordant in Natural Dyes from Mangrove Extract (Rhizophora mucronata) - W. Pancapalaga; E. Ishartati; T. Ambarwati (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study evaluated the color fastness and crust quality of eco-printed leather using various types of mordant in the natural dye of mangrove extract. This study used 20 sheepskin crusts and mangrove bark extract. This experimental study employed a Completely Randomized Design (CRD) with different mordant types as the treatments. The types of mordant used were Aluminum Sulfate (Al2(SO4)3), Calcium Carbonate (CaCO3), Citric Acid (C6H8O7), and Ferrous Sulfate (FeSO4). The results showed that the use of Ferrous Sulfate (FeSO4) as a mordant gave a darker color and produced better color fastness on eco-printed leather to dry and wet rubbing with a value of 5 (very good), to washing with a value of 4-5 (good), and to sweat with a value of 5 (very good). The use of Ferrous Sulfate (FeSO4) as a mordant improved the tensile strength (p= 0.078), decreased the elongation (p= 0.008), increased the elasticity (p= 0.000), and increased the cracking resistance (p= 0.013) of the eco-printed leather as well as produced more stable stitch-tear strength of the eco-printed leather. It is concluded that using Ferrous Sulfate (FeSO4) as a mordant gives a brownish yellow color, increases color fastness to wet rubbing, dry rubbing, washing, sweating, improves crust qualities especially tensile strength and cracking resistance, and decreases the elongation of eco-printed leather.